Comparison of White Matter Structure of Drug-Naïve Patients With Bipolar Disorder and Major Depressive Disorder Using Diffusion Tensor Tractography - Koreki, Akihiro; Niida, Richi; Niida, Akira; Yamagata, Bun; Anamizu, Sachiko; Mimura, Masaru (Frontiers in Psychiatry, 2022)
BACKGROUND: The presence of microstructural white matter (WM) abnormalities in individuals with bipolar disorder (BD) have been reported. However, no study has compared the differences in WM structure among drug-naïve BD, drug-naïve major depression disorder (MDD), and healthy controls (HC) using the visual evaluation method of diffusion tensor tractography (DTT). METHODS: This retrospective study included 12 drug-naïve patients with BD, 15 with MDD, and 27 age- and sex-matched HC. Visual evaluation, fractional anisotropy (FA), and apparent diffusion coefficient (ADC) were analyzed in the anterior thalamic radiation (ATR), cingulate fasciculus, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, uncinate fasciculus, and fornix using the optimal follow-up truncation threshold. RESULTS: No significant differences were found regarding the FA or ADC of any tract. However, visual evaluation revealed poor depiction of ATR in patients with BD compared to MDD and HC (p = 0.004), and post hoc analysis showed a significant difference between BD and HC (p = 0.018). CONCLUSIONS: The visual evaluation method of DTT revealed poor depiction of ATR in patients with BD compared to HC and MDD, suggesting microstructural WM abnormalities of ATR in BD.